High-Throughput Sequencing Analysis of the Actinobacterial Spatial Diversity in Moonmilk Deposits - Marta Maciejewska; Magdalena Całusińska; Luc Cornet; Delphine Adam; Igor S. Pessi; Sandrine Malchair; Philippe Delfosse; Denis Baurain; Hazel A. Barton; Monique Carnol; Sébastien Rigali (MDPI AG, 2018)
Moonmilk are cave carbonate deposits that host a rich microbiome, including antibiotic-producing Actinobacteria, making these speleothems appealing for bioprospecting. Here, we investigated the taxonomic profile of the actinobacterial community of three moonmilk deposits of the cave "Grotte des Collemboles" via high-throughput sequencing of 16S rRNA amplicons. Actinobacteria was the most common phylum after Proteobacteria, ranging from 9% to 23% of the total bacterial population. Next to actinobacterial operational taxonomic units (OTUs) attributed to uncultured organisms at the genus level (~44%), we identified 47 actinobacterial genera with Rhodoccocus (4 OTUs, 17%) and Pseudonocardia (9 OTUs, ~16%) as the most abundant in terms of the absolute number of sequences. Streptomycetes presented the highest diversity (19 OTUs, 3%), with most of the OTUs unlinked to the culturable Streptomyces strains that were previously isolated from the same deposits. Furthermore, 43% of the OTUs were shared between the three studied collection points, while 34% were exclusive to one deposit, indicating that distinct speleothems host their own population, despite their nearby localization. This important spatial diversity suggests that prospecting within different moonmilk deposits should result in the isolation of unique and novel Actinobacteria. These speleothems also host a wide range of non-streptomycetes antibiotic-producing genera, and should therefore be subjected to methodologies for isolating rare Actinobacteria.